Scalp reconstruction by tissue expansion: tips and tricks - Raposio, Edoardo; Raposio, Giorgio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Numerous details regarding preoperative planning of scalp expansion are of the utmost importance for maximizing the results of this procedure. Methods: The purpose of this paper is to describe the tips and tricks useful for obtaining the best results in scalp expansion. Results: Basic concepts and operative technique are discussed and detailed. Conclusions: In scalp reconstruction, the use of tissue expansion allows to obtain successful results, Anyhow, it is mandatory to follow some basic rules, dictated by anatomical, technical, and psychological considerations.